DETERMINATION OF INTERNET USAGE STATUS OF PARENTS WHOSE CHILDREN ARE BEING TREATED IN PEDIATRICS CLINIC REGARDING THEIR CHILDREN'S DISEASES - ÇİĞDEM, Zerrin; DOĞAN, Fatih; Melike (Göbeklitepe Medical Science Journal, 2024)
This study was planned to determine the internet usage status of parents whose children are being treated in the pediatric clinic regarding their children's diseases.The population of the descriptive research was 1176 parents, while the sample was 1017 parents. Research data were collected with a data collection form.The average age of hospitalized children was 6.45±1.50 years. It was observed that 34.4% of the parents did research on the internet about their child's illness. It was observed that there was a statistically significant relationship between parents' internet use and their educational status. Children with acute and chronic diseases, obtaining information about the child's illness, getting information about the child's illness on the internet, researching on the internet ensures being prepared for a doctor's appointment, sufficient information on the internet, the effect of the internet environment on hospital selection, communicating with the doctor on the internet, the child's It was observed that there was a statistical significance when compared in terms of curiosity about new developments regarding the disease. As a result, the comparison of parents' internet usage characteristics regarding the child's illness and the child's illness type (acute/chronic) was determined to be meaningful.